1989
DOI: 10.1017/s0022112089001424
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatile flow through constricted tubes: an experimental investigation using photochromic tracer methods

Abstract: A photochromic tracer method has been used to record pulsatile flow velocity profiles simultaneously at three axial locations along a flow channel. Two major advantages of this multiple-trace method are that it enables velocity data to be acquired in an efficient non-invasive manner and that it provides a detailed description of the spatial relationship of the flow field. The latter is found to be particularly useful in the investigation of transitional type flows; for example, in describing coherent flow stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
84
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(99 citation statements)
references
References 27 publications
15
84
0
Order By: Relevance
“…In these experiments, an identical cast model to the cell culture model was perfused with a solution of odorless mineral spirits (Shell-Sol 715) and trace amounts of colourless dye (1′,3′,3′-trimethylindoline-6-nitro-benzospiropyran). When exposed to UV light from a laser, the solution turns opaque and forms a photochromic trace (21)(22)(23)(24). A CCD camera (Dalsa Pantera TF IM60, Dalsa) and an image-processing board (National Instruments PCI 1428) were used to track the molecular displacement and calculate the wall shear rate.…”
Section: Wall Shear Stress Determinationmentioning
confidence: 99%
“…In these experiments, an identical cast model to the cell culture model was perfused with a solution of odorless mineral spirits (Shell-Sol 715) and trace amounts of colourless dye (1′,3′,3′-trimethylindoline-6-nitro-benzospiropyran). When exposed to UV light from a laser, the solution turns opaque and forms a photochromic trace (21)(22)(23)(24). A CCD camera (Dalsa Pantera TF IM60, Dalsa) and an image-processing board (National Instruments PCI 1428) were used to track the molecular displacement and calculate the wall shear rate.…”
Section: Wall Shear Stress Determinationmentioning
confidence: 99%
“…Sankar presented a developed analysis of impulsive flow affection by a turbulence method that via associating their results with ours it is concluded that for every value of index, in some points of the pulse which the velocity was high, maximum shear stress increased and vice versa (in some points of the pulse with a low velocity, maximum shear stress was decreased). These results revealed that impulsive flow can cause returned flow (in maximum discharge) after the obstruction which calculating the amounts seems to be necessary to optimize bypass surgical operations 16 .…”
Section: Discussionmentioning
confidence: 91%
“…We have expressed the pulsatility in the flow through a variation in Reynolds number [14,45] around a mean Reynolds number (Re mean ) of 200. The Reynolds number (Re = ρud/μ) is defined on the basis of the diameter of the unstenosed artery, time-averaged mean velocity of flow, and the density and viscosity of blood, which are taken as ρ = 1056 Kg/m 3 and μ = .00345 PaS, respectively.…”
Section: Physical Modelmentioning
confidence: 99%
“…Ahmed and Giddens [16] used ultrasound and laser Doppler techniques to analyze the flow disturbances and wall shear stress associated with the presence of stenoses. The photochromic tracer method used by Ojha et al [14] enabled the description of coherent flow structures present in the pulsatile poststenotic flow field. Siouffi et al [17] and Deplano and Siouffi [18] used the pulsed Doppler ultrasonic velocimetry for the measurement of velocity and determination of wall shear stress around the zone of stenosis, while Brunette et al [19] used particle image velocimetry to find out the wall shear stress distribution and secondary flow associated with a mild stenosis in a phantom coronary artery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation